Taxonomic evaluation of the marsupial frog Gastrotheca peruana (Amphibia: Hemiphractidae) based on mitochondrial 16S rRNA gene - Rodriguez, Daniel (2019)
The taxonomic status of Gastrotheca peruana is evaluated using phylogenetic methods and 16S gene sequences. The maximum likelihood and Bayesian trees showed that the genetic variants of G. peruana form two clades that are not sister to each other. One of these clades is present in northern Perú and includes a specimen collected at the type locality of G. peruana dissimilis. The other clade is restricted to central Peru and contains individuals from type localities of two nominal forms, G. p. peruana and G. p. junensis, and is sister to G. aratia. Our results suggest that G. peruana sensu lato currently encompass two species. We restrict Gastrotheca peruana to populations from central Perú (departments of Ancash, Lima, Pasco and Junín) and assign populations from departments of La Libertad and Cajamarca to Gastrotheca dissimilis.